Ethico-Legal Aspects Of Personal Data Protection In Indonesia - Yovita Arie Mangesti; Slamet Suhartono; Ahmad Mahyani (International Journal of Educational Research & Social Sciences, 2021)
Protection of personal data is a manifestation of the state's role in protecting human rights. The use of electronic data on the one hand provides convenience, especially in terms of accessibility of public services, but on the other hand electronic data leakage is a violation of ethics and law. This paper is a normative legal research that examines the ethical aspects of personal data protection in Indonesia with a statutory approach and a conceptual approach. There is an ethical and legal correlation that should be the legal ratio of personal data protection, so that in order to provide legal protection not only through the formation of laws but also the efforts of the information commission agency to educate the public that ethically the misuse of one's personal data for commodities is a non-legal act. ethical behavior that exploits and demeans human dignity, which must be accounted for. Protection of personal data is realized by making crimes against personal data a common offense, and providing public accessibility to obtain advocacy whenpersonal data is misused in order to achieve the value of justice and legal protection.